PENGARUH PROFITABILITAS, SOLVABILITAS, RENTABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Nafiatul Khikmah; Muhamad Yusuf; Yohani Yohani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
The aim of this study is to investigate the effect of profitability, solvability, liquidity, the company size, investment decisions on company value. The population of this study was manufacturing companies listed in Indonesia Stock Exchange for the period 2015-2018. It’s totally was 45 companies. The samples of this study were 15 companies. The sampling method used was purposive sampling. The data collected from annual financial report in IDX website. The result of this study showed that profitability, rentability, and the company size had a positive and significant effect on company value. The significance value of those three variables were 0,020; 0,003; and 0,000. Otherwise, the solvability, liquidity and investment decision had no effect on it. The significance value of those variables was 0,759; 0,444; and 0,584. Meanwhile, the adjusted test result was 0,346. Its mean company value affected by profitability, solvability, rentability, liquidity, the company size and investment decision 34,6%